Romanian migrants' journeys as transformational entrepreneurs in London - Iuliana Maria Chitac (CES Working Papers, 2022)
Migrant entrepreneurship is recognized as an essential economic driver for host and home countries. However, Eastern European entrepreneurs' social initiatives and contributions are rarely acknowledged, shadowed by their image of precarity and economic survival in host countries. This Interpretative Phenomenological Study (IPA) challenges this paucity by investigating how 18 London-based Romanian migrant entrepreneurs interviewed (LRMEs) enable transformational entrepreneurial practices transcending their "individual subsistence to create jobs and income for others" (Schoar, 2010, p.5) and contributing positively to Britain's social fiber. Specifically, this interdisciplinary study draws on Berry's acculturation model (1997, 2003, 2005) and social learning and self-efficacy theories (Bandura, 1971, 1977). This article contributes to the nascent transformational entrepreneurship scholarship and practice (TE) and policy. Specifically, it demonstrates how these Romanian migrant entrepreneurs enable acculturative belonging for themselves and other stakeholders as they enact through their everyday transformational entrepreneurship practices of role modelling, encouraging other migrants to pursue a social- economic entrepreneurial path and acculturative mentoring, supporting them to become custodians of bicultural values and customs, empowered to address social injustice and discrimination.
Keywords: 330; interpretative phenomenological analysis; migrant entrepreneurship; transformational leadership